2005
DOI: 10.1063/1.2012531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dislocations on photoluminescence of InGaN∕GaN multiple quantum wells

Abstract: A methodology for the determination of the subsurface line direction of dislocations using scanning tunneling microscopy (STM) images is presented. The depth of the dislocation core is derived from an analysis of the displacement field measured by STM. The methodology is illustrated for dislocations at GaN(10 10) cleavage surfaces. It is found that the dislocation line bends toward the surface, changing from predominantly edge-type to more screw-type character, when approaching the intersection point. Simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…where i ¼ 1 or 2, À i0 represents the energy broadening due to temperature-independent mechanisms such as impurities, 27) dislocations, 28,29) electron interaction and Auger processes, 30) À iLO is the energy broadening caused by the electron (excitonic)-LO phonon interaction, and  iLO corresponds to the LO phonon temperature. The solid curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…where i ¼ 1 or 2, À i0 represents the energy broadening due to temperature-independent mechanisms such as impurities, 27) dislocations, 28,29) electron interaction and Auger processes, 30) À iLO is the energy broadening caused by the electron (excitonic)-LO phonon interaction, and  iLO corresponds to the LO phonon temperature. The solid curves in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, some statistical investigations propose that the threading dislocations having a screw-component Burgers vector act as non-radiative centers in GaN epitaxial layers [11]. Hacke et al [12] On the other hand, Zhang et al [6] have found that threading edge dislocations act as non-radiative recombination centers. The CL measurements also show that threading edge dislocations in InGaN/GaN QW structure act as non-radiative recombination centers [13].…”
Section: Dislocations and Near-band Edge Luminescencementioning
confidence: 98%
“…We have investigated the PL integrated intensity of a series of InGaN/GaN multiple quantum wells (MQWs) as a function of dislocation density [6]. The deep energy levels and non-radiative recombination centers occurring at dislocation lines were believed to result in the reduction of band edge emission intensity.…”
Section: Dislocations and Near-band Edge Luminescencementioning
confidence: 99%
“…Considering the low reflectivity of the uncoated cavity facets of the LD, this low Characteristics of InGaN multiple quantum well blue-violet laser diodes 731 threshold current density indicates that the MQW active layer had high internal quantum efficiency and low optical loss. Zhang et al [14] revealed by TAXRD and PL measurements that InGaN/GaN MQWs with a longer period grown on a high quality GaN template in our laboratory had less interface roughness and a lower edge dislocation density, and also had a higher PL intensity. These characteristics of the MQWs can give rise to high internal quantum efficiency and low optical loss of the MQW active layer and result in a low threshold current density and high characteristic temperature of the LD.…”
mentioning
confidence: 96%
“…There are several factors that influence the characteristics of such LDs, but the quality of the MQW plays a dominant role in the improvement of the LDs. By the systematic optimization of the MQWs, it is found that MQWs with a longer period have better photoluminescence characteristics [14] . We have realized an LD structure with this kind of MQW, and here we report our results.…”
mentioning
confidence: 99%